Iterative reconstruction of SiPM light response functions in a square-shaped compact gamma camera. (5th April 2017) - Morozov, A; Alves, F; Marcos, J; Martins, R; Pereira, L; Solovov, V; Chepel, V
Abstract: Compact gamma cameras with a square-shaped monolithic scintillator crystal and an array of silicon photomultipliers (SiPMs) are actively being developed for applications in areas such as small animal imaging, cancer diagnostics and radiotracer guided surgery. Statistical methods of position reconstruction, which are potentially superior to the traditional centroid method, require accurate knowledge of the spatial response of each photomultiplier. Using both Monte Carlo simulations and experimental data obtained with a camera prototype, we show that the spatial response of all photomultipliers (light response functions) can be parameterized with axially symmetric functions obtained iteratively from flood field irradiation data. The study was performed with a camera prototype equipped with a 30  ×  30  ×  2 mm 3 LYSO crystal and an 8  ×  8 array of SiPMs for 140 keV gamma rays. The simulations demonstrate that the images, reconstructed with the maximum likelihood method using the response obtained with the iterative approach, exhibit only minor distortions: the average difference between the reconstructed and the true positions in X and Y directions does not exceed 0.2 mm in the central area of 22  ×  22 mm 2 and 0.4 mm at the periphery of the camera. A similar level of image distortions is shown experimentally with the camera prototype.